Positive effects of white tea on breast cancer: N-methyl-N-nitrozourea intraductal induced breast carcinoma model - Sibel Mataraci Karakas; Adnan Yilmaz; Tolga Mercantepe; Atilla Topcu; Esra Pinarbas (Journal of Functional Foods)
An objective of this study was to investigate the chemopreventive and therapeutic effects of white tea (WT) on breast cancer.Fifty Sprague-Dawley rats were divided into five groups: control, MNU, taxol, low dose white tea (LWTE) and high dose white tea (HWTE). Either tap water or WT was given by oral gavage for 4 weeks. At the end of this period, mammary carcinoma was induced in all groups except the control group. Then oral gavage continued for 14 weeks. For laboratory analyses, blood and mammary tissues were collected.LWTE was determined to prevent lipid peroxidation, DNA and protein damage, reduce inflammatory cytokine levels, prevent cancer cell proliferation by inducing apoptosis, inhibit tumour growth by blocking M-CSF release and NRP-2 activity. Hyperplasia and histopathological changes increased by MNU exposure were successfully repaired with WT.The results of our study show that WT has positive effects in preventing and treating breast cancer.